Expression and localization of axin 2 in colorectal carcinoma and its clinical implication - Schaal, Ute; Grenz, Sandra; Merkel, Susanne; Rau, Tilman; Hadjihannas, Michel; Kremmer, Elisabeth; Chudasama, Priya; Croner, Roland S.; Behrens, Jürgen; Stürzl, Michael; Naschberger, Elisabeth (International Journal of Colorectal Disease, 2013)
Purpose: Aberrant activation of the Wnt/β-catenin pathway plays a major role in the development of colorectal carcinoma (CRC). Axin 2 is a key protein of this pathway and is upregulated in CRC. Here, we investigated RNA- and protein expression of axin 2 in CRC tissues at the single cell level. Moreover, the association of axin 2 with prognosis and survival was investigated in a large cohort of CRC patients (n = 280). Methods: Localization and expression of axin 2 and β-catenin was investigated using in situ hybridization and immunohistochemical staining. The quantitative expression levels of axin 2 were determined using RT-qPCR. The association of axin 2 expression with prognosis and survival of the patients was determined by statistical analysis (logrank test, Kaplan-Meier). Results: Our results confirmed the upregulation of axin 2 in CRC and showed that it is broadly expressed in the cytoplasm of the tumor epithelial cells both, in the tumor center and at the invasion front. Axin 2 was rarely expressed by tumor stromal cells and only weakly by normal colonic epithelial cells. Staining of β-catenin and axin 2 in consecutive CRC tissue sections revealed that nuclear translocation of β-catenin in the tumor front was not associated with changes in the cytoplasmic localization of axin 2. Axin 2 did not show any association with proven prognostic factors or survival of the CRC patients. Conclusion: The generally increased expression of axin 2 in all tumor stages as compared to normal tissue suggests an initiating pathogenic function in the development of CRC. © 2013 Springer-Verlag Berlin Heidelberg.
Created from Fastlane, Scopus look-up
Keywords: β-Catenin; Axin 2; Colorectal carcinoma; Wnt/β-catenin signaling

O-GlcNAc transferase inhibits KSHV propagation and modifies replication relevant viral proteins as detected by systematic O-GlcNAcylation analysis. - Jochmann, Ramona; Pfannstiel, Jens; Chudasama, Priya; Kühn, Elisabeth; Konrad, Andreas; Stürzl, Michael (Glycobiology, 2013)
O-GlcNAcylation is an inducible, highly dynamic and reversible post-translational modification, mediated by a unique enzyme named O-linked N-acetyl-d-glucosamine (O-GlcNAc) transferase (OGT). In response to nutrients, O-GlcNAc levels are differentially regulated on many cellular proteins involved in gene expression, translation, immune reactions, protein degradation, protein-protein interaction, apoptosis and signal transduction. In contrast to eukaryotic cells, little is known about the role of O-GlcNAcylation in the viral life cycle. Here, we show that the overexpression of the OGT reduces the replication efficiency of Kaposi's sarcoma-associated herpesvirus (KSHV) in a dose-dependent manner. In order to investigate the global impact of O-GlcNAcylation in the KSHV life cycle, we systematically analyzed the 85 annotated KSHV-encoded open reading frames for O-GlcNAc modification. For this purpose, an immunoprecipitation (IP) strategy with three different approaches was carried out and the O-GlcNAc signal of the identified proteins was properly controlled for specificity. Out of the 85 KSHV-encoded proteins, 18 proteins were found to be direct targets for O-GlcNAcylation. Selected proteins were further confirmed by mass spectrometry for O-GlcNAc modification. Correlation of the functional annotation and the O-GlcNAc status of KSHV proteins showed that the predominant targets were proteins involved in viral DNA synthesis and replication. These results indicate that O-GlcNAcylation plays a major role in the regulation of KSHV propagation.

Reverse transfected cell microarrays in infectious disease research - Konrad, Andreas; Jochmann, Ramona; Kühn, Elisabeth; Naschberger, Elisabeth; Chudasama, Priya; Stürzl, Michael (Methods in Molecular Biology, 2011)
Several human pathogenic viruses encode large genomes with often more than 100 genes. Viral pathogenicity is determined by carefully orchestrated co-operative activities of several different viral genes which trigger the phenotypic functions of the infected cells. Systematic analyses of these complex interactions require high-throughput transfection technology. Here we have provided a laboratory manual for the reverse transfected cell microarray (RTCM; alternative name: cell chip) as a high-throughput transfection procedure, which has been successfully applied for the systematic analyses of single and combination effects of genes encoded by the human herpesvirus-8 on the NF-kappaB signal transduction pathway. In order to quantitatively determine the effects of viral genes in transfected cells, protocols for the use of GFP as an indicator gene and for indirect immunofluorescence staining of cellular target proteins have been included. RTCM provides a useful methodological approach to investigate systematically combination effects of viral genes on cellular functions.
Created from Fastlane, Scopus look-up
Keywords: Cell chip; High-throughput; Human herpesvirus-8; KSHV; Microarray; Transfection

Structural proteins of Kaposi's sarcoma-associated herpesvirus antagonize p53-mediated apoptosis - Chudasama, Priya; Konrad, A.; Jochmann, R.; Lausen, Berthold; Holz, Patrick; Naschberger, Elisabeth; Neipel, Frank; Britzen-Laurent, Nathalie; Stürzl, Michael (Oncogene, 2015)
The tumor suppressor p53 is a central regulatory molecule of apoptosis and is commonly mutated in tumors. Kaposi's sarcoma-associated herpesvirus (KSHV)-related malignancies express wild-type p53. Accordingly, KSHV encodes proteins that counteract the cell death-inducing effects of p53. Here, the effects of all KSHV genes on the p53 signaling pathway were systematically analyzed using the reversely transfected cell microarray technology. With this approach we detected eight KSHV-encoded genes with potent p53 inhibiting activity in addition to the previously described inhibitory effects of KSHV genes ORF50, K10 and K10.5. Interestingly, the three most potent newly identified inhibitors were KSHV structural proteins, namely ORF22 (glycoprotein H), ORF25 (major capsid protein) and ORF64 (tegument protein). Validation of these results with a classical transfection approach showed that these proteins inhibited p53 signaling in a dose-dependent manner and that this effect could be reversed by small interfering RNA-mediated knockdown of the respective viral gene. All three genes inhibited p53-mediated apoptosis in response to Nutlin-3 treatment in non-infected and KSHV-infected cells. Addressing putative mechanisms, we could show that these proteins could also inhibit the transactivation of the promoters of apoptotic mediators of p53 such as BAX and PIG3. Altogether, we demonstrate for the first time that structural proteins of KSHV can counteract p53-induced apoptosis. These proteins are expressed in the late lytic phase of the viral life cycle and are incorporated into the KSHV virion. Accordingly, these genes may inhibit cell death in the productive and in the early entrance phase of KSHV infection.
EVALuna2:8221